2016
DOI: 10.1007/s13187-016-1086-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Practices, Knowledge, Confidence, and Attitude toward Oral Cancer among Oral Health Professionals between Japan and Australia

Abstract: The purpose of this study was to investigate the practices, knowledge, confidence, and attitude toward oral cancer among Japanese oral health professionals (J-OHPs) and to identify Japanese-specific problems in oral cancer practices by comparing them between Japan and Australia. A questionnaire survey regarding oral cancer practices among Australian oral health professionals (Au-OHPs) was conducted in Australia in 2014-2015. The questionnaire was translated into Japanese, and a Web-based questionnaire survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 16 publications
7
33
3
Order By: Relevance
“…Likewise, dentists' attitude and skills regarding oral cancer practice are crucial in their engaging in such behaviors [19]. Results of the present study are in line with previously published findings in relation to dentists' limited performance of full clinical oral cancer examination and patients' education of oral cancer related risk factors [20]. If the faculty members do not perform full clinical oral cancer examination and patients' education about its related risk factors, such behavior can be crosstransmitted to their dental students [21].…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, dentists' attitude and skills regarding oral cancer practice are crucial in their engaging in such behaviors [19]. Results of the present study are in line with previously published findings in relation to dentists' limited performance of full clinical oral cancer examination and patients' education of oral cancer related risk factors [20]. If the faculty members do not perform full clinical oral cancer examination and patients' education about its related risk factors, such behavior can be crosstransmitted to their dental students [21].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a personal interview may explain the high response rate of the current study, which was too close to studies performed in Iran and showed about 92% response rate (Mehdizadeh, Seyed Majidi, Sadeghi, & Hamzeh, ; Razavi et al, ). In contrast, several previously published articles in Brazil, Japan, Australia, and Spain showed a much lower response rate of less than 10% due to the dependence on sent electronic mails (Haresaku, Makino, Sugiyama, Naito, & Marino, ; Lopez‐Jornet et al, ; Pavao Spaulonci, Salgado de Souza, Gallego Arias Pecorari, & Lauria Dib, ). It was found that 82.25% of the dentists identified OSCC as the most common cancer of the oral cavity.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have been carried out in several parts of the world, indicating dentists' poor or lacking knowledge regarding oral cancer [ 2 , 14 , 18 , 20 – 25 ]. In Brazil, some studies have been performed using a questionnaire previously published in the study of Dib et al [ 19 ], which, at that time, demonstrated the low level of professional knowledge on this theme [ 8 , 26 – 29 ].…”
Section: Introductionmentioning
confidence: 99%